Prolate and Temperature‐Responsive Self‐Assemblies of Amphiphilic Random Copolymers with Perfluoroalkyl and Polyoxyethylene Side Chains in Solution. Issue 15 (2nd July 2018) - Martinelli, Elisa; Guazzelli, Elisa; Galli, Giancarlo; Telling, Mark T. F.; Poggetto, Giovanni Dal; Immirzi, Barbara; Domenici, Fabio; Paradossi, Gaio
Abstract: Two amphiphilic random copolymers, PEGMAx‐ co ‐FAy ( x = 90 and 70 mol%), are synthesized by ATRP and their solutions are investigated as a function of solvent, concentration, and temperature by DLS and SANS analyses. Both copolymers self‐assemble in nanostructures by single‐chain folding in water solutions over a wide range of temperatures. The values of the DLS hydrodynamic radius and the SANS radius of gyration are found to be ≈4 nm and ≈3.4–3.7 nm, respectively. Moreover, SANS shows the self‐folded nanoassemblies to be prolated spheroids with a ratio of polar/equatorial axes of ≈5:1 for PEGMA90‐ co ‐FA10 and ≈2:1 for PEGMA70‐ co ‐FA30. On heating above a critical temperature T c, multichain microassemblies are formed that revert back to nanoassemblies on cooling below T c . This temperature‐responsive transition is fully and sharply reversible. Abstract : DLS and SANS analyses of ATRP amphiphilic random copolymers show the existence of nanoassemblies via spontaneous single‐chain folding in water and other solvents over a wide temperature range. The nanoassemblies are prolated spheroids in D2 O. At a critical temperature, multichain microassemblies are formed that fully and sharply revert back to single‐chain nanoassemblies.